2016
DOI: 10.2174/1568026616666160719163839
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Non-Catalytic Cysteine Residues Through Structure-Guided Drug Discovery

Abstract: The targeting of non-catalytic cysteine residues with small molecules is drawing increased attention from drug discovery scientists and chemical biologists. From a biological perspective, genomic and proteomic studies have revealed the presence of cysteine mutations in several oncogenic proteins, suggesting both a functional role for these residues and also a strategy for targeting them in an ‘allele specific’ manner. For the medicinal chemist, the structure-guided design of cysteine-reactive molecules is an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 88 publications
0
58
0
Order By: Relevance
“…This has been exploited for finding inhibitors of the DUB Usp7, for example, which show efficacy in tumor models [209][210][211][212]. There is precedent for bringing thiol-reactive drugs to the clinic [213][214][215][216][217]. The recent development of AMG 510 by Amgen for treating solid tumors with a particular KRAS-G12C mutation further demonstrates that cysteine-reactive drugs can advance to clinical trials [218].…”
Section: Inhibiting Other Ups Componentsmentioning
confidence: 99%
“…This has been exploited for finding inhibitors of the DUB Usp7, for example, which show efficacy in tumor models [209][210][211][212]. There is precedent for bringing thiol-reactive drugs to the clinic [213][214][215][216][217]. The recent development of AMG 510 by Amgen for treating solid tumors with a particular KRAS-G12C mutation further demonstrates that cysteine-reactive drugs can advance to clinical trials [218].…”
Section: Inhibiting Other Ups Componentsmentioning
confidence: 99%
“…Another approach is the use of antibodies to block the host-pathogen interaction [3], as well as nanobodies that overcome the limitations of traditional monoclonal antibodies and peptides as therapeutics [29,30]. An alternative approach that is prompted by identifying the importance of the CL1 disulfide bond in this study, and also avoids the limitations of other strategies, is to design small molecules that target and reduce the disulfide bond [31,32], thus preventing H. pylori binding; an approach that has previously been used to target HIV infection [33,34]. In this context, a previous study showed that binding of the H. pylori adhesin BabA to its cellular receptor Le b was impaired by the reduction in a conserved 8-residue cysteine-clasped loop in the adhesins glycan-binding site [8].…”
Section: Discussionmentioning
confidence: 99%
“…The last decade has seen an increase in the development of covalent inhibitors as potential therapeutic agents. This interest has been driven by an appreciation of the advantages of covalent mechanisms of inhibition [1][2] , including the ability to overcome resistance, such as in EGFR gatekeeping mutations 3 , the opportunity to increase affinity for otherwise 'undruggable' targets, and distinct pharmacokinetic properties due to very long target-residency times [4][5] . A barrier to the pursuit of such compounds has been the perception that electrophilic drugs present greater risk due to nonspecific binding to off-targets, formation of reactive metabolites, or rapid inactivation by reaction with glutathione or other endogenous nucleophiles [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Interest in covalent drugs is driven by an appreciation of the advantages of covalent mechanisms of inhibition. These advantages are well reviewed 5,6 and include the ability to overcome resistance, such as in EGFR gatekeeping mutations 7 , a method to increase affinity for otherwise 'undruggable' targets, and distinct pharmacokinetic requirements owing to very long target residency times of covalent drugs 8, 9 . As interest in covalent drug discovery has grown, so have analytical techniques for the screening of covalent small molecules and the size of electrophilic compound libraries. Despite these improvements, the largest reported screen of a covalent library is of just 1000 compounds 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation